2022
DOI: 10.1108/mhrj-11-2021-0084
|View full text |Cite
|
Sign up to set email alerts
|

Mood Lifters: evaluation of a novel peer-led mental wellness program

Abstract: Purpose The purpose of this paper is to test a mental wellness intervention, Mood Lifters (ML), that addresses significant barriers to mental health care. ML includes adults over 18 struggling with mental wellness or any life difficulties, except those with active suicidality, mania and psychosis, and addresses barriers to care using peer leaders in a manualized group format with a gamified point system. Design/methodology/approach Participants were recruited using online postings. Those eligible (76% female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 42 publications
(52 reference statements)
2
29
0
Order By: Relevance
“…Mood Lifters for Seniors was adapted from an existing mental wellness program developed by two study co-authors (PJD and CMV). The original Mood Lifters program was developed iteratively through reviews of best practices in behavior change, positive psychology, and clinical interventions (e.g., cognitive-behavioral therapy [CBT] and dialectical behavior therapy), along with several pilot groups and revisions that culminated in a randomized control trial (Votta & Deldin, 2022). The Mood Lifters program consists of 15 weekly, hour-long peer-led meetings, with a focus on peer support and accountability for at-home practice of skills learned during group meetings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mood Lifters for Seniors was adapted from an existing mental wellness program developed by two study co-authors (PJD and CMV). The original Mood Lifters program was developed iteratively through reviews of best practices in behavior change, positive psychology, and clinical interventions (e.g., cognitive-behavioral therapy [CBT] and dialectical behavior therapy), along with several pilot groups and revisions that culminated in a randomized control trial (Votta & Deldin, 2022). The Mood Lifters program consists of 15 weekly, hour-long peer-led meetings, with a focus on peer support and accountability for at-home practice of skills learned during group meetings.…”
Section: Methodsmentioning
confidence: 99%
“…Between meetings, members practice skills taught in group sessions and track them through a point system (e.g., 30 minutes of aerobic exercise counts as one point). In the original trial of the program, participants reported statistically significant improvements in anxiety, and those who completed more points or homework also reported statistically significant reductions in depression and perceived stress (Votta & Deldin, 2022). In the current study, we describe our adaptation of the Mood Lifters program for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…For this adaptation of the Mood Lifters program, all ML-GS leaders were also graduate students. Previous research on Mood Lifters found that Mood Lifters peer leaders are equally effective as professional leaders (i.e., clinically trained) in facilitating these groups (Votta & Deldin, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Modeled after the successful Kids’ Club program for children exposed to family violence (Graham-Bermann et al, 2007, 2015; Howell et al, 2015, 2013) and the Mood Lifters (Votta, 2020) program for adults, the primary mission of the Kids’ Empowerment Program (KEP; Graham-Bermann, 2018) is to enhance the well-being of school-age children while building their social, emotional, and coping skills. The 12-session KEP provides support and information while teaching children self-management skills based on techniques derived from a combination of best, evidence-based practices (e.g., using elements of cognitive behavioral therapy (CBT, Beck, 2011), behavioral activation (BA, Mazzucchelli, 2016), brief BA (Funderburk et al, 2020), and interpersonal therapy (IPT, Cuijpers et al, 2016)).…”
Section: Taking a Public Health Approachmentioning
confidence: 99%